2009
DOI: 10.1017/s1355770x09990027
|View full text |Cite
|
Sign up to set email alerts
|

Biofuels, poverty, and growth: a computable general equilibrium analysis of Mozambique

Abstract: ABSTRACT. This paper assesses the implications of large-scale investments in biofuels for growth and income distribution. We find that biofuels investment enhances growth and poverty reduction despite some displacement of food crops by biofuels. Overall, the biofuel investment trajectory analyzed increases Mozambique's annual economic growth by 0.6 percentage points and reduces the incidence of poverty by about 6 percentage points over a 12-year phase-in period. Benefits depend on production technology. An out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
97
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(102 citation statements)
references
References 7 publications
4
97
1
Order By: Relevance
“…As shown in Table 1, a majority of their populations are smallholder farmers living in rural areas, where they rely on rainfed agriculture and are subject to frequent weather shocks and food shortages. The main food crops are maize and cassava, which Arndt et al (2010aArndt et al ( , 2010b.…”
Section: Biofuels In Mozambique and Tanzaniamentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Table 1, a majority of their populations are smallholder farmers living in rural areas, where they rely on rainfed agriculture and are subject to frequent weather shocks and food shortages. The main food crops are maize and cassava, which Arndt et al (2010aArndt et al ( , 2010b.…”
Section: Biofuels In Mozambique and Tanzaniamentioning
confidence: 99%
“…Investors are particularly interested in Mozambique. By 2009 the country's government had received requests for 12 million hectares of state-owned land to produce feedstock, of which two million hectares of requests were considered credible (Arndt et al 2010a). By contrast, the interest in Tanzania has been more modest.…”
Section: Biofuels In Mozambique and Tanzaniamentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the assumption that prices in other markets stay unchanged and that income effects are negligible, is questionable. Especially when questions about economic growth or income distribution are addressed, a general equilibrium framework seems more appropriate (Arndt et al, 2010).…”
Section: Linking Life Cycle Assessment To Partial Equilibrium Modelsmentioning
confidence: 99%
“…Furthermore, biofuels may support agriculture by providing job opportunities, new investment and revitalization of rural areas (Klenschmit, 2007). Arndt et al (2010) found that biofuels production increased economic growth by a half a percentage point each year highlighted that developing countries can take this as an opportunity to promote development. While there is a growing body of literature on the usefulness of biofuels, a number of criticism have been recorded as well.…”
Section: Introduction 11 mentioning
confidence: 99%